Blog i jego odmiany – internetowy ekshibicjonizm? Przyczyny rozwoju i żywotności tej formy komunikacji - Szendzikowska, Agata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
Blog is a frequent, chronological publication of personal thoughts and Web links. Web journal is often a mixture of what is happening in a person’s life and what is happening on the Web, a kind of hybrid diary/guide site, although there are as many unique types of blogs as there are people. People maintained blogs long before the term was coined, but the trend gained momentum with the introduction of automated published systems. Thousands of people use services such as OnetBlog to simplify and accelerate the publishing process. Starting a new blog is quite difficult and take some time. So this can put many people off, there are then other people who have blogs with no comments or visits. Most of people want to stand out from this crowd of millions of bloggers, and they really want to be one of the few hundred thousand blogs that are actually visited. Desire of become a blog star is very strong, so owners of Web diaries are determined to promote their sites. How far they can go to be world - famous?